Visible-Light Photocatalytic Degradation of Metronidazole Using Bismuth Oxide-Doped Erbium Oxide Anchored Graphene Oxide Nanocomposites: Kinetics and Mechanism - Nada D. Ali; Usama Akram Saed; Waqar A. Abdulnabi; Zeyad Zeitoun (Bulletin of Chemical Reaction Engineering & Catalysis, 2026)
Metronidazole (MNZ) is a persistent pharmaceutical contaminant that resists conventional wastewater treatment. In this work, a visible-light-active Bi2O3–Er2O3/graphene oxide (GO) nanocomposite was synthesized by a co-precipitation method.  This nanocomposite was evaluated for the photocatalytic degradation of MNZ in aqueous solution. Structural and optical characterization (XRD, FTIR, SEM, TEM, BET, PL, and UV–Vis DRS) confirmed the successful anchoring of Bi2O3–Er2O3 nanoparticles onto GO sheets. That resulted in improved visible-light absorption and blocked charge-carrier recombination. The composite containing 20 wt% GO showed the highest photocatalytic activity. It achieved near-complete MNZ removal under exposure to visible light. The improved performance was attributed to the combined effects of many factors. Those include Bi2O3–Er2O3-induced visible-light response, Er2O3-assisted charge trapping, and efficient electron transport through GO. The study included examining the effects of many factors. Those included the solution pH, catalyst dosage, initial MNZ concentration, and GO content. Optimal degradation was found in alkaline conditions. The catalyst was found to be stable and reusable. Therefore, it has high potential for sustainable antibiotic removal from wastewater. Copyright © 2026 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).